1999
DOI: 10.1074/jbc.274.6.3513
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Inhibiting the Collagen Binding Function of Integrin α2I Domain

Abstract: Integrin ␣ 2 subunit forms in the complex with the ␤ 1 subunit a cell surface receptor binding extracellular matrix molecules, such as collagens and laminin-1. It is a receptor for echovirus-1, as well. Ligands are recognized by the special "inserted" domain (I domain) in the integrin ␣ 2 subunit. Venom from a pit viper, Bothrops jararaca, has been shown to inhibit the interaction of platelet ␣ 2 ␤ 1 integrin with collagen because of the action of a disintegrin/metalloproteinase named jararhagin. The finding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 40 publications
0
86
0
Order By: Relevance
“…In line with this, the inhibitory effect of the metalloprotease jararhagin, which binds to the I domain of the a2-subunit and proteolytically breaks down the b1 subunit, is also overcome by high concentrations of collagen. Ivaska et al [39] have also reported that a cyclic peptide based on the active sequence of jararhagin only partially inhibits aggregation but causes a complete inhibition of binding of collagen to the a2-subunit. These data demonstrate that high concentrations of collagen are able to overcome the inhibitory effect of blockade of binding to a2b1, through interaction with a second receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, the inhibitory effect of the metalloprotease jararhagin, which binds to the I domain of the a2-subunit and proteolytically breaks down the b1 subunit, is also overcome by high concentrations of collagen. Ivaska et al [39] have also reported that a cyclic peptide based on the active sequence of jararhagin only partially inhibits aggregation but causes a complete inhibition of binding of collagen to the a2-subunit. These data demonstrate that high concentrations of collagen are able to overcome the inhibitory effect of blockade of binding to a2b1, through interaction with a second receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning and Mutagenesis of the Human Integrin ␣ 2 I Domain-Human integrin ␣ 2 I domain was generated as described earlier by Ivaska et al (24). The integrin ␣ 2 cDNA was a gift from Dr. M. Hemler, Dana Farber, Boston.…”
Section: Methodsmentioning
confidence: 99%
“…Other proteases than MMPs may also interact with integrins. These include uPA/uPAR, which may interact with several integrins (Aguirre Ghiso et al, 1999;Carriero et al, 1999;Wei et al, 2001;Wei et al, 1996;Xue et al, 1997), elastase with α M β 2 integrin (Cai and Wright, 1996), snake venom disintegrin/metalloproteinase with α 2 β 1 integrin (Ivaska et al, 1999) and ADAMs with several integrins (Bax et al, 2004;Bridges et al, 2002;Nath et al, 1999).…”
Section: Other Proteases In Cell Migration and Invasionmentioning
confidence: 99%